Musculoskeletal Problems and Work-Related Factors Among Middle-Aged Rural Homemakers (Journal of Preventive and Social Medicine, 2025)
Background: Bangladeshi rural women, who spend 14-20 hours daily on homemaking duties, often suffer from musculoskeletal problems due to poor ergonomics and repetitive actions. These disorders affect productivity and quality of life due to lack of awareness and preventive measures. The study aims to assess musculoskeletal problem prevalence among middle-aged rural homemakers, identify contributing factors, and recommend health interventions. Methods: A cross-sectional study was conducted in Dohar Upazila, Bangladesh to find out musculoskeletal problems and work-related factors among middle-aged rural homemakers. The study covered 121.41 square kilometers and involved face-to-face interviews and a semi-structured questionnaire. Data were analyzed for accuracy, outliers, inconsistencies and missing values. The study aimed to assess the relationship between musculoskeletal problems and personal, socio-demographic and work-related factors. Results: The study surveyed 347 respondents aged 30-59 years, with 49.6% falling within the 30-39 age groups. The majority was Muslim, 38.2% completed primary education, and 88.8% were married. Family structures consisted of 64.0% nuclear and 36.0% joint families. Health issues included asthma (13.3%), heart disease (10.1%), hypertension (29.7%), diabetes (17.0%), osteoarthritis (52.4%), previous trauma (18.2%), and rheumatoid arthritis (6.1%). Musculoskeletal problems were most prevalent (74.0%) among individuals aged 30- 39, with married individuals reporting the highest incidence (83.4%??). Factors such as awkward work posture, forceful exertion and weight handling were found to be significant (p